Automatic Transfer Switch (ATS) Using Omron CP1L PLC and Human Machine Interface - Suhanto, Suhanto; Faizah, Fiqqih (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Airports in aviation services are required to use facilities with the latest technology. This requires a stable and uninterrupted electricity supply to operate correctly. The Automatic Transfer Switch design based on the CX-Designer Human Machine Interface moves the electrical power supply source from PLN to the Generator Set or vice versa. There are two operating modes, namely manual mode and auto mode. In operation, it is also equipped with an interlock function between the PLN contactor and the generator and a PLN phase loss sensor for the R, S and T phases. For auto mode, it uses a timer with a setting for PLN of 12 seconds and for the generator of 15 seconds. The control system uses an Omron CP1L-L20DR-D PLC with CX-Programmer programming for Human Machine Interface with CX-Designer. The Automatic Transfer Switch test was successful in system testing, starting from manual and auto mode, PLN phase loss testing, and timer testing; 100% of the entire hardware and software system ran well.